2009
DOI: 10.1007/978-1-60327-993-2_9
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Mitosis with Laser Microsurgery and RNAi in Drosophila Cells

Abstract: Progress from our present understanding of the mechanisms behind mitosis has been compromised by the fact that model systems that were ideal for molecular and genetic studies (such as yeasts, C. elegans or Drosophila) were not suitable for intracellular micromanipulation. Unfortunately, those systems that were appropriate for micromanipulation (like newt lung cells, PtK1 cells or insect spermatocytes) are not amenable for molecular studies. We believe that we can significantly broaden this scenario by developi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…The inclusion of a kinetochore marker in this study and the observed variability of inter-kinetochore distance after k-fiber cut explains previous observations in which no detectable kinetochore relaxation was observed without the use of a kinetochore marker [29]. Laser microsurgery was performed essentially as described in [373]. …”
Section: Figuresupporting
confidence: 52%
“…The inclusion of a kinetochore marker in this study and the observed variability of inter-kinetochore distance after k-fiber cut explains previous observations in which no detectable kinetochore relaxation was observed without the use of a kinetochore marker [29]. Laser microsurgery was performed essentially as described in [373]. …”
Section: Figuresupporting
confidence: 52%
“…mNeonGreen-PICH cells were imaged every 60s at 4 z-sections at 1 μm intervals. The laser microsurgery was conducted as described previously (Pereira et al, 2009) and is detailed in the Supplemental Experimental Procedures. An extended description of the analysis of the time-lapse movies and kinetochore motion is also included in the Supplemental Experimental Procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Examples of mechanical approaches to improve live cell imaging include: coating coverslips (e.g. with Poly-L-Lysine) to help keep dividing cells flat; confining dividing cells in PDMS devices of different heights (Le Berre, Aubertin and Piel, 2012); and laying an agar pad on top of a cell to reduce mitotic rounding and movement (Fukui, Yumura and Yumura 1987; Pereira, Matos, Lince-Faria and Maiato, 2009). Examples of physical perturbation approaches include microneedles to exert and measure tension on individual chromosomes and kinetochores in insect spermatocyte cells (Nicklas, 1983; Nicklas and Staehly, 1967); optical tweezers to move chromosomes inside mammalian cells (Liang, Wright, He and Berns, 1991); and laser ablation to probe kinetochore motility (Khodjakov and Rieder, 1996), kinetochore signaling (Rieder, Cole, Khodjakov and Sluder, 1995) and spindle mechanics (Snyder, Armstrong, Stonington, Spurck and Pickett-Heaps, 1991).…”
Section: Spindle Compression To Image and Perturb Kinetochoresmentioning
confidence: 99%